Response of improved Sweetpotato varieties to weevils, Cylas species infestation in Coastal Tanzania - Gration M. Rwegasira (Journal of Pure and Applied Agriculture, 2023)
Field experiments were conducted at Tanzania Agricultural Research Institute (TARI-Kibaha) from October 2014 to July 2015 to assess the impact of sweetpotato weevil, Cylas puncticollis and C. brunneus infestation and damage on yield of selected improved varieties; Ukerewe, Simama, Mataya and Kiegea. Experiments were laid out in randomised complete block design (RCBD) with sweetpotato varieties as treatments. About 30cm long sweetpotato vines were collected from a three-month aged crop maintained as nursery in screen-house. Results revealed that all varieties were susceptible to weevils’ infestation albeit at varied degrees. Orange fleshed varieties; Mataya and Kiegea yielded higher (2.02 ton/ha and 1.76 ton/ha) than white fleshed varieties; Simama and Ukerewe (1.66 ton/ha and 1.53 ton/ha) respectively and were less susceptible to sweetpotato weevils’ infestation. Highly significant (p<0.001) variation among tested varieties in terms of yield (number of harvested tubers) was recorded. There was a positive correlation between yield and percentage infestation, suggesting that weevils exert significant impacts on sweetpotato yield in costal Tanzaniathus, the need to prioritize the management of the pest whenever the crop is grown. Orange fleshed varieties are likely to increase sweetpotato production through increased yield per unit area. Therefore, they should be complemented with other management practices that have been shown to reduce weevil damage.